Metabolic Profiling Analysis of the Alleviation Effect of Treatment with Baicalin on Cinnabar Induced Toxicity in Rats Urine and Serum - Su, Guangyue; Chen, Gang; An, Xiao; Wang, Haifeng; Pei, Yue-Hu (Frontiers in Pharmacology, 2017)
Objectives Baicalin is the main bioactive flavonoid constituent isolated from Scutellaria baicalensis Georgi. The mechanisms of protection of liver remain unclear. In this study, 1H NMR-based metabonomics approach has been used to investigate the alleviation effect of Baicalin. Method 1H NMR metabolomics analyses of urine and serum from rats, was performed to illuminate the alleviation effect of Baicalin on mineral medicine (cinnabar)-induced liver and kidney toxicity. Results The metabolic profiles of groups receiving Baicalin at a dose of 80 mg/kg were remarkably different from cinnabar, and meanwhile, the level of endogenous metabolites returned to normal compared to group cinnabar. PLS-DA scores plots demonstrated that the variation tendency of control and Baicalein are apart from Cinnabar. The metabolic profiles of group Baicalein were similar to those of group control. Statistics results were confirmed by the histopathological examination and biochemical assay. Conclusion Baicalin have the detoxification effects to the liver and kidney damage induced by cinnabar. The Baicalin could regulate endogenous metabolites associated with the energy metabolism, choline metabolism, amino acid metabolism and gut flora.